A Critical Discourse Analysis of Ideology in the Song “Where Is the Love?” by The Black Eyed Peas Based on van Dijk’s Theory - Juliana Tifani; Tiodor Sihotang; Sry Tama Butar Butar; Partohap Saut Raja Sihombing (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the ideology embedded in the song “Where Is the Love?” by The Black Eyed Peas using Critical Discourse Analysis (CDA) based on van Dijk’s socio-cognitive model. Discourse analysis is concerned with how language is used to construct meaning, ideology, and social realities. Song lyrics, as a form of written discourse, often function as a medium for expressing social criticism and ideological perspectives. Therefore, this study focuses on revealing how ideological meanings are represented in the song lyrics. This research employs a qualitative research design with document analysis as the data collection technique. The data consist of selected lyric lines from the song “Where Is the Love?” that reflect social issues. The data are analyzed using van Dijk’s three analytical dimensions: textual structure, social cognition, and social context. The findings reveal that the song conveys strong ideological messages related to humanitarian values, peace, equality, and social justice. The lyrics criticize violence, racism, discrimination, and political hypocrisy, encouraging listeners to reflect critically on global social problems. The study concludes that song lyrics can function as powerful social discourse that shapes social awareness and ideology. This research contributes to discourse analysis studies by demonstrating the applicability of van Dijk’s Critical Discourse Analysis framework to song lyrics as a form of social and ideological expression.